2006
DOI: 10.1021/ja0625430
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthetic Access to the Hetisine C20-Diterpenoid Alkaloids. A Concise Synthesis of Nominine via Oxidoisoquinolinium-1,3-Dipolar and Dienamine-Diels−Alder Cycloadditions

Abstract: A concise synthetic approach to the hetisine C20-diterpenoid alkaloids is reported. The total synthesis of (+/-)-nominine was accomplished in a 15-step sequence employing a dual cycloaddition strategy. Key features of the synthesis include a reversible intramolecular 4-oxidoisoquinolinium betaine dipolar cycloaddition in conjunction with a pyrrolidine-induced dienamine isomerization/Diels-Alder cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…[40] An edge-on conformational view of nominine (7) revealed two promising key elements for simplification, namely the bridging pyrrolidine embedded in the azabicyclo[3.2.1]octane core, as well as the cyclohexane moiety within the bicyclo[2.2.2]octane substructure of 7. The former could be constructed via an earlystage intramolecular 1,3-dipolar cycloaddition (i.e., 20) with an endocyclic 1,3-dipole, thereby rapidly establishing the entire N-heterocyclic array within the alkaloid target.…”
Section: Introductionmentioning
confidence: 99%
“…[40] An edge-on conformational view of nominine (7) revealed two promising key elements for simplification, namely the bridging pyrrolidine embedded in the azabicyclo[3.2.1]octane core, as well as the cyclohexane moiety within the bicyclo[2.2.2]octane substructure of 7. The former could be constructed via an earlystage intramolecular 1,3-dipolar cycloaddition (i.e., 20) with an endocyclic 1,3-dipole, thereby rapidly establishing the entire N-heterocyclic array within the alkaloid target.…”
Section: Introductionmentioning
confidence: 99%
“…In their seminal work, (±)-nominine ( 225 ) was synthesized within 40 steps and 0.15% overall yield. Two years later, a more concise and efficient access to (±)-nominine ( 225 ), featuring a oxidoisoquinolinium-1,3-dipolar cycloaddition and a dienamine-Diels–Alder reaction, was accomplished by Gin (Scheme 31) [178]. Coupling of 235 and 236 , both synthesized within three steps from simple starting materials, via a Staudinger–aza-Wittig reaction gave amine 237 as a mixture of four diastereoisomers.…”
Section: Reviewmentioning
confidence: 99%
“…[4a] Several groups have developed both inter-and intramolecular [5 + 2] cycloadditions of oxidopyridinium ions with various alkenes, and some of these reactions have constituted key steps in the syntheses of important natural products, such as tricyclic cocaine analogues, [76] sarains, [77] and more recently the hetisine alkaloid nominine. [78] In 2006, Curtis et al reported an asymmetric version of the [5 + 2] cycloaddition of oxidopyridinium ions. [79] Thus, a chiral 3-oxidopyridinium betaine 110, bearing a chiral auxiliary on the nitrogen of the betaine, was prepared and subsequently submitted to [5 + 2] cycloaddition with tert-butyl acrylate.…”
Section: A C H T U N G T R E N N U N G [5+2] Cycloadditions Of Oxidopmentioning
confidence: 99%